Supports for migrant farmworkers: tensions in (in)access and (in)action. Issue 4 (10th December 2020) - Caxaj, Susana; Cohen, Amy; Marsden, Sarah
Abstract : Purpose: This study aims to examine the role of support actors in promoting or hindering access to public services/spaces for migrant agricultural workers (MAWs) and to determine the factors that influence adequate support for this population. Design/methodology/approach: Using a situational analysis methodology, the authors carried out focus groups and interviews with 40 support actors complimented by a community scan (n = 28) with public-facing support persons and a community consultation with migrant farmworkers (MFWs) (n = 235). Findings: Two major themes were revealed: (In)access and (In)action and Blurred Lines in Service Provision. The first illustrated how support actors could both reinforce or challenge barriers for this population through tensions of "Coping or Pushing Back on Constraints" and "Need to find them first!" Justification or Preparation? Blurred lines in Service Provision encompassed organizational/staff's behaviors and contradictions that could hinder meaningful support for MFWs revealing two key tensions: "Protection or performance?" and "Contradicting or reconciling priorities? Our findings revealed a support system for MAWs still in its infancy, contending with difficult political and economic conditions. Social implications: Service providers can use research findings to improve supports for MAWs. For example, addressing conflicts of interests in clinical encounters and identification of farms to inform adequate outreach strategies can contribute to more effective support for MAWs. Originality/value: This research is novel in its examination of multiple sectors as well as its inclusion of both formal and informal actors involved in supporting MAWs. Our findings have the potential to inform more comprehensive readings of the health and social care resources available to MAWs.